The ocean of God : on the transreligious future of religions - Faber, Roland, 1960- (Anthem Press, 2019)
'The Ocean of God' proposes that the future of religions will become transreligious. Its polyphilic pluralism, entertaining religious pluralism and the unity of religions mediated by process and Baha'i thought, assumes the spiritual impulse of humanity, despite secularizations, naturalizations and transhumanist dreams, to further a civilized future of peace.